2014
DOI: 10.1088/0264-9381/31/24/245006
|View full text |Cite
|
Sign up to set email alerts
|

Juggled interferometer for the detection of gravitational waves around 0.1–10 Hz

Abstract: We propose a novel type of earthbound gravitational wave detector targeting a frequency band of 0.1–10 Hz. By using repeatedly free falling test masses—juggling—one can in principle decouple test masses from the seismically noisy environment and avoid suspension thermal noise in a straightforward manner. As a consequence, the measurement process will not be continuous anymore. We show that to a given extent, continuous signals can be extracted from the discontinuous data by removing a linear trend for the data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…They focus largely on the astrophysical sources in their sensitivity band. Although their optimistic estimate of performance was excellent at low frequency, it relied upon the use of a freely floating test mass, a technology that has only been proposed and has no further development so far [20]. The conservative estimate they make is similar to the one we reach here, without focusing on the technical details needed to reach that.…”
Section: Introductionmentioning
confidence: 72%
“…They focus largely on the astrophysical sources in their sensitivity band. Although their optimistic estimate of performance was excellent at low frequency, it relied upon the use of a freely floating test mass, a technology that has only been proposed and has no further development so far [20]. The conservative estimate they make is similar to the one we reach here, without focusing on the technical details needed to reach that.…”
Section: Introductionmentioning
confidence: 72%
“…Instruments that measure the acceleration are called gravimeters. A test mass inside a gravimeter can be freely falling such as atom clouds (Zhou et al 2011) or, as suggested as possible future development, even macroscopic objects (Friedrich et al 2014). Typically though, test masses are supported mechanically or magnetically constraining motion in some of its degrees of freedom.…”
Section: Gravity Acceleration and Tidal Forcesmentioning
confidence: 99%
“…Instruments that measure the acceleration are called gravimeters. A test mass inside a gravimeter can be freely falling such as atom clouds [181] or, as suggested as possible future development, even macroscopic objects [72]. Typically though, test masses are supported mechanically or magnetically constraining motion in some of its degrees of freedom.…”
Section: Gravity Measurementsmentioning
confidence: 99%